SELF-CARE MANAJEMEN GLUKOSA DAN PENGENDALIAN DIET SEBAGAI UPAYA PENGENDALIAN KADAR GLUKOSA DARAH PENYANDANG DIABETES MELLITUS - Asyrofi, Ahmad; Arisdiani, Triana; Widiastuti, Yuni Puji (LPPM STIKES MUHAMMADIYAH GOMBONG, 2018)
The phenomenon of the number of people with diabetes mellitus (DM) in theworld today is increasing along with socio-cultural changes, and the largenumber of people with DM who are undiagnosed becomes increasinglypotential to cause further complications. Self-care glucose management anddietary control are part of the pillars in DM care. The aim of the study was todetermine differences in blood glucose management and dietary controlbetween uncontrolled glycemic (HbA1c > 7%) and controlled glycemic(HbA1c â‰¤ 7%). The study uses a case control design. The sample of this studywas DM patients with adult and elderly age of 104 samples including: 52uncontrolled glycemic groups and 52 controlled glycemic groups, withconvinience techniques. The research tool uses Diabetes Self-ManagementQuestionnaire (DSMQ) subscale glucose management and dietary control.Data analysis using Mann-Whitney U Test. The results showed significantdifferences in glucose management (p = 0.034) and dietary control (p = 0.001)between uncontrolled glycemic groups and controlled glycemic groups.Recommended for people with diabetes mellitus to improve glucosemanagement self-care activities and dietary control to control glycemic(HbA1c â‰¤ 7). Subsequent research needs to look for factors that predict glucosemanagement and dietary control for people with diabetes.